2003
DOI: 10.17221/5437-agricecon
|View full text |Cite
|
Sign up to set email alerts
|

Food expenditures of Czechs' households and Engel's law

Abstract: Abstract:The paper is focused on the analysis of Engel's Law validity within food expenditures of Czech households. The realised research dealt with the impacts of real income sizes of the average Czech household on its real shares of food expenditures in [1995][1996][1997][1998][1999][2000][2001][2002]. The evaluation of Engel's Law validity was based on the regression demand model with the regressor -real income and the regressant -real food share. Because the Czech Statistical Office database had a time dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
0
5
0
1
Order By: Relevance
“…Women in the low-income group had less varied diets than females in the higherincome groups, except for fish and fruit. Syrovátka (2003) examined the impact of the czech household income differentiation on the food expenditures using the Engel's expenditure functions. his research results confirmed the negative correlation between the level of the household incomes and the level of expenditures spent on such kind of food groups as fish and fish products, fruit and fruit products, fats and oils.…”
mentioning
confidence: 99%
“…Women in the low-income group had less varied diets than females in the higherincome groups, except for fish and fruit. Syrovátka (2003) examined the impact of the czech household income differentiation on the food expenditures using the Engel's expenditure functions. his research results confirmed the negative correlation between the level of the household incomes and the level of expenditures spent on such kind of food groups as fish and fish products, fruit and fruit products, fats and oils.…”
mentioning
confidence: 99%
“…These starting points make the household's decision-making process formally tractable and enable its precise mathematical formalization. This advantage of the neoclassical approach is demonstrated for example in Syrovátka (2003) by the analysis of the Engel's law validity within food expenditures. However, the agents usually do not know all possible events or their accompanying probabilities and the market forces generally cannot account for the unknowability and unpredictability of the future.…”
mentioning
confidence: 99%
“…Přímá dynamizace modelů sice zamezila vzniku zdánlivých regresí v analyzovaných vztazích z pozice trendové složky (Minařík, B., 1998), ale nedokázala eliminovat případný vliv pravidelně se opakujících výkyvů. Bohužel právě přítomnost periodické složky může vyvolat nežádoucí zkreslení zkoumaných Engelových vztahů, viz výsledky výzkumů v oblasti výdajů českých domácností za potraviny (Syrovátka, P., 2003). S vědomím této skutečnosti byla ve výchozích časových řadách (re t ), (rE t ), (rm t ) nejprve důkladně prošetřena periodická složka vývoje tak, aby mohlo být provedeno její případné odfiltrování.…”
Section: Materiál a Metodikaunclassified